EHCM: A Multihop Aided Wireless Routing Protocol Based on Flow Priority in Smart Grid - Xiaobin Tan; Qin Zheng; Ling Liu (International Journal of Distributed Sensor Networks)
In traditional smart grid, data aggregator (DA) and distribution box (DB) send the data collected by sensors to base station (BS) through cellular interface, which is called single-hop communication mode (SCM). In smart grid, different data packets have different delay priorities and the BS cannot satisfy all the delay requirements of different data because of limited resources through SCM. In order to meet the QoS requirements of different priority data, we propose a new scheme: enhanced hybrid communication mode (EHCM), by introducing multihop communication mode (MCM) into this scenario to improve the network's performance by adding another wireless interface on each node. Our scheme EHCM consists of two parts: the intracell data transmission and the cell edge data transmission. In the first part, we propose a solution to choose a relay node according to the node's energy consumption and its residual energy and a solution to forward packets based on its priority and residual lifetime (RLT). In the second part, the tasks of data transmission can be delivered from the congested DB nodes to the adjacent idle ones to provide optimal performance. At last, the simulation shows that our scheme can satisfy the performance requirement of smart grid.